Analysis of Dampers for Stay Cables Using Non Linear Beam Elements. (November 2018) - Battini, Jean-Marc
Abstract: This paper presents a numerical approach to evaluate the damping properties of a stay cable with an external viscous damper. The idea is to model the cable by using non-linear corotational beam elements and to study small vibrations around the static deformed equilibrium configuration. This gives a complex eigenvalue problem from which the modal damping ratios can be calculated. The performance of the proposed method is assessed through two numerical applications. Compared with the analytical methods based on differential equations widely used in the literature, the proposed non-linear finite element approach has the advantages that the effect of the sag is considered in an accurate way and that there is no limitation regarding the number and the value of the structural parameters that can be introduced in the model.